2015
DOI: 10.1371/journal.ppat.1005143
|View full text |Cite
|
Sign up to set email alerts
|

Cullin4 Is Pro-Viral during West Nile Virus Infection of Culex Mosquitoes

Abstract: Although mosquitoes serve as vectors of many pathogens of public health importance, their response to viral infection is poorly understood. It also remains to be investigated whether viruses deploy some mechanism to be able to overcome this immune response. Here, we have used an RNA-Seq approach to identify differentially regulated genes in Culex quinquefasciatus cells following West Nile virus (WNV) infection, identifying 265 transcripts from various cellular pathways that were either upregulated or downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Infection of live mosquitoes with ZIKV and treatment with the IR inhibitor Eight to ten, 5-8 day old female mosquitoes of the Higgs and Brisbane strains (kindly provided by Dr. Ary Hoffmann, University of Melbourne, Australia, and Dr Akbari, University of California, respectively), were starved the day before being challenged with an virus-infected blood meal containing 10 5.6 TCID 50 (50 percent tissue culture infectious dose)/mL, through membrane feeding using chicken blood and skin (Paradkar et al, 2015). Chicken blood and skin were provided by the Small Animal Facility of the Australian Animal Health Laboratory from chicken bred in the laboratory with no sign of arboviral infection.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Infection of live mosquitoes with ZIKV and treatment with the IR inhibitor Eight to ten, 5-8 day old female mosquitoes of the Higgs and Brisbane strains (kindly provided by Dr. Ary Hoffmann, University of Melbourne, Australia, and Dr Akbari, University of California, respectively), were starved the day before being challenged with an virus-infected blood meal containing 10 5.6 TCID 50 (50 percent tissue culture infectious dose)/mL, through membrane feeding using chicken blood and skin (Paradkar et al, 2015). Chicken blood and skin were provided by the Small Animal Facility of the Australian Animal Health Laboratory from chicken bred in the laboratory with no sign of arboviral infection.…”
Section: Methods Detailsmentioning
confidence: 99%
“…376 Similar results were obtained in human THP-1 cells infected by an antibody-dependent route, 377 and the proteasome inhibitors, bortezomib and MG132, were shown to reduce infection by DENV, ZIKV, and WNV. 378,379 Notably, other groups have reported that the ubiquitin system is important for early events in flavivirus infections. Wang et al showed that several proteasome inhibitors caused internalized JEV particles to be mislocalized to lysosomes, resulting in loss of infection.…”
Section: Pro-viral Host Factorsmentioning
confidence: 99%
“…This includes TotM during early stages of infection (24) and vir-1 during later stages (12) (Figure 2D). JAK/STAT has been shown to be involved in the immune response against the insect virus Drosophila C virus but not SINV (24) in Drosophila, and JAK/STAT is antiviral against WNV in both Drosophila and Culex mosquitoes (10,50).…”
Section: Jak/stat Pathwaymentioning
confidence: 99%